Astragalus mongholicus Bunge and Curcuma aromatica Salisb. modulate gut microbiome and bile acid metabolism to inhibit colon cancer progression - Wang, Xu; Zhu, Boyang; Hua, Yongzhi; Sun, Ruolan; Tan, Xiying; Chang, Xiangwei; Tang, Decai; Gu, Junfei (Frontiers in Microbiology, 2024)
Abstract: Alterations in the gut microbiome and bile acid metabolism are known to play a role in the development and progression of colon cancer. Medicinal plants like Astragalus mongholicus Bunge and Curcuma aromatica Salisb.(AC) have shown preferable therapeutic effect on cancer therapy, especially digestive tract tumors like colon cancer. However, the precise mechanisms of AC inhibiting colon cancer, particularly in relation to the gut microbiome and bile acid dynamics, are not fully understood. Our research aimed to investigate the anti-tumor properties of AC in mice with CT26 colon cancer and further investigate its underlying mechanism via intestinal microbiota. The size and pathological changes of solid tumors in colon cancer are used to evaluate the inhibitory effect of AC on colon cancer. Metagenomics and 16s rRNA gene sequencing were employed to clarify the dysbiosis in the gut microbiome of colon cancer and its impact on colon cancer. The levels of bile acids (BAs) in the feces of mice from each group were measured using UPLC-Qtrap-MS/MS. AC effectively suppressed the growth of colon cancer and reduced histological damage. Notably, AC treatment led to changes in the gut microbiome composition, with a decrease in pathogenic species like Citrobacter and Candidatus_Arthromitus, and an increase in beneficial microbial populations including Adlercreutzia, Lachnospiraceae_UCG-001, and Parvibacter. Additionally, AC altered bile acid profiles, resulting in a significant decrease in pro-carcinogenic bile acids such as deoxycholic acid (DCA) and lithocholic acid (LCA), while increasing the concentration of the cancer-inhibitory bile acid, ursodeoxycholic acid (UDCA). Tracking and analyzing the data, AC may mainly upregulate FabG and baiA genes by increasing the relative abundance of Adlercreutzia and Parvibacter bacteria, which promoting the metabolism of pro-carcinogenic LCA. These findings provide strong evidence supporting the role of AC in regulating gut microbiome-mediated bile acid metabolism, which is crucial in impeding the progression of colon cancer.